2013
DOI: 10.4071/isom-2013-wa21
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Variable Frequency Microwave Underfill Processing and High Performance Packaging Materials

Abstract: Variable frequency microwave (VFM) has been recently proposed as an alternative underfill curing method that provides flip chip package warpage improvement as well as potential underfill cure time reductions. The current paper outlines how such advantages in VFM processing of underfill can be compromised when applied to high performance organic packages. VFM recipes for three underfill materials were developed by performing several VFM curing runs followed by curing rate measurements using the differential sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Indeed, the severity and the failures seen after 1500 cycles were comparable for the three cure profiles, therefore for both cure methods. A more clear difference was seen in the work of Diop et al where, for the type of package and UF material tested, the VFM cured packages demonstrated a better mechanical reliability than the convection cured package due to a lower post cure storage modulus [16]. Nevertheless, the fact that the optimized VFM profiles proposed here did not impair reliability is of particular interest in that these profiles were carried out in the absence of a prior package bake-out.…”
Section: Adhesion and Reliability Testsmentioning
confidence: 61%
See 4 more Smart Citations
“…Indeed, the severity and the failures seen after 1500 cycles were comparable for the three cure profiles, therefore for both cure methods. A more clear difference was seen in the work of Diop et al where, for the type of package and UF material tested, the VFM cured packages demonstrated a better mechanical reliability than the convection cured package due to a lower post cure storage modulus [16]. Nevertheless, the fact that the optimized VFM profiles proposed here did not impair reliability is of particular interest in that these profiles were carried out in the absence of a prior package bake-out.…”
Section: Adhesion and Reliability Testsmentioning
confidence: 61%
“…VFM heats absorbing polymers faster than convection resulting in faster processing times. For instance, at the same convection cure temperatures, VFM is usually seen to reach a full cure of the UF with only 10% of the recommended convection time [16]. Also, VFM demonstrates a full cure of the UF at lower temperatures within times similar to that of convection cure [16].…”
Section: B Cure Methodsmentioning
confidence: 95%
See 3 more Smart Citations